1977
DOI: 10.1007/bf02773619
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory effect of sulpiride on cinchophen gastric ulceration in dogs

Abstract: An intraventricular administration of sulpiride suppressed the experimental cinchophen ulcer, thereby the effect of repeated administration of the material on cinchophen ulcerogenesis is evident, whereas intermittent administration lacked this effect. Such an effect as reducing experimental cinchophen ulceration, which is due to central neurohumoral mechanism, following intraventricular infusion of sulpiride appears to be ascribable to a chemical blockage of the hypothalamic structure. It can thus be concluded… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
8
0

Year Published

1978
1978
1999
1999

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 7 publications
1
8
0
Order By: Relevance
“…On the other hand, in patients with chronic gastric ulcer, pepsin concentration in gastric juice was relatively high just before operation, while plasma corticosteroid levels were normal. Previous work by one of us [3] showed that emotional factors associated with anticipation of an operation are capable of increasing the gastric pepsin level and, to a lesser degree, the gastric acid level in patients with chronic peptic ulcer. A further increase in pepsin secretion was observed after abdominal incision in patients with chronic peptic ulcer.…”
Section: Discussionmentioning
confidence: 92%
See 4 more Smart Citations
“…On the other hand, in patients with chronic gastric ulcer, pepsin concentration in gastric juice was relatively high just before operation, while plasma corticosteroid levels were normal. Previous work by one of us [3] showed that emotional factors associated with anticipation of an operation are capable of increasing the gastric pepsin level and, to a lesser degree, the gastric acid level in patients with chronic peptic ulcer. A further increase in pepsin secretion was observed after abdominal incision in patients with chronic peptic ulcer.…”
Section: Discussionmentioning
confidence: 92%
“…As soon as the entire mucosal surface pH was determined by the method of Nagamachi and Skoryna [10,11], a section of gastric mucosa was cut away from the underlying submucosa and divided into 1 cm 2 pieces, weighed accurately to the nearest 0.1 g and kept at -20~ until it was homogenized at 0-4~ in 5 ml distilled water. The homogenate was diluted 1 to 50 with 0.01 N HCI, centrifuged (3,000 rpm for 5 minutes), and a quantitative measurement of the peptic activity of fundic mucosal pepsinogen was performed by the same method as used for gastric juice [4,9]. It should be emphasized that similar activities of pepsin have been calculated from mucosa and juice.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations